KẾT QUẢ NGHIÊN CỨU BƯỚC ĐẦU VỀ THÀNH PHẦN LOÀI KHU HỆ NẤM LỚN TẠI VƯỜN QUỐC GIA CÁT BÀ - Phạm, Thị Hà Giang (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
INITIAL RESEARCH FINDINGS OF THE SPECIES COMPOSITION OF MACROFUNGI FLORA IN CAT BA NATIONAL PARK The study was conducted in Cat Ba National Park from June/2012 to June/2013. According to the initial research results, a total of 52 macrofungi species in 23 families and 11 orders have been found there. Two species Auricularia auricula and Mycroporus xanthopus have been found in all habitats. Among 11 identified orders, Poliporales and Agaricales are the most diverse orders (71.15% of total species) whereas 5 others (Boletales, Dacrymycetales, Hemenochaetales, Pezizales and Thelephorales) have the poorest biodiversity in Cat Ba National Park (1.92% of all recorded species). Of 52 recorded macrofungi species 22 are edible or can be used as medicine or both, 2 are toxic and the rest are wood destroyer or of unknown effect.